5-(4-Hydroxyphenyl)-3H-1, 2-dithiole-3-thione-based fibrates as potential hypolipidemic and hepatoprotective agents. Issue 23 (15th December 2018) - Chen, Zi-Zhang; Xie, Yun-Dong; Shao, Li-Hua; Wang, Qiu-Tang; Xu, Yan-Hong; Bian, Xiao-Li
Graphical abstract: Highlights: Design of 5-(4-hydroxyphenyl)-3 H -1, 2-dithiole-3-thione derivatives with a significantly hypolipidemic activity. Study indicated that tested compound also showed hepatoprotective activity in hyperlipidaemia. The tested compound displayed potent antioxidant and anti-inflammatory activities. Abstract: Hypolipidemic effects of the newly synthesized 5-(4-hydroxyphenyl)-3 H -1, 2-dithiole-3-thione-based fibrates were evaluated in Triton WR-1339 and high-fat diet (HFD)-induced hyperlipidemic mice. Preliminary screening of all the synthesized compounds was done by using an acute model (Triton WR-1339 model), in which compound6 shown more significant antidyslipidemic activity than fenofibrate (FF). The compound6 was also found to reduce serum triglyceride (TG), total cholesterol (TC) and low density lipoprotein cholesterin (LDL) in HFD-induced hyperlipidemic mice. Moreover, compound6 displayed hepatoprotective effect, a significant amelioration in hepatic indices (AST and ALT) toxicity was observed and the histological examination showed that compound6 inhibited the development of hepatic lipid accumulation and ameliorated the damage in hepatic tissue compared to model mice. Additional effects such as the potent antioxidant and anti-inflammatory action confirmed and reinforced the efficacy of compound6 as a new agent of dual-effect hypolipidemic and hepatoprotective activities.